KEARIFAN LOKAL MARAPU MENDUKUNG HINDU NUSANTARA - I Wayan Suarjaya (Widya Sandhi: Jurnal Kajian Agama, Sosial dan Budaya, 2020)
West Sumba people with trust in Marapu who were given various titles such as Magholo Marawi, Mori, and so on were believed to be in control of the inner life of the believers. On this basis, the adherents of the Marapu faith are convinced that there is a power above him, who has power over his life. Also convinced of the existence of sin due to actions and rituals of peace, convinced of the existence of human spirits, other spirits, and natural souls. For the good life of the Marapu believers, they strive to always harmonize their lives with Marapu and other spirits and natural souls by carrying out rituals which they call cultural activities. The concept of harmonization between humans is also taught in the Marapu belief conveyed by adherents of that belief from generation to generation through word of mouth without written sources. The harmony of the relationship is reflected in cultural activities, among others, in the implementation of marriage rituals, pregnancy, and birth rituals and the equal relationship between adherents of the faith and between the residents of the Marapu faiths and the Rato . Harmonization of human relations with nature by the Marapu belief community is felt to be very important so that they continue to strive to maintain harmony in the relationship. The harmonization with nature is like harmony with water or rivers or lakes or seas, harmony with forests, harmony with the earth and mountains. The behavior of harmonization is carried out through traditional Merapu ritual activities such as betel nut betel offerings accompanied by slaughter of animals delivered by the original Sumba language prayer Such is the paper that can be conveyed, the conclusion Marapu supports Hindu Nusantara, which is adopted by the Persada Nusantara from Sabang to Merauke, especially the Sumba people, most of whom still believe in the Marapu local authenticity that is preserved and its sustainability.